Enhancing Inclusive Health Service Delivery Through Capacity Building for Health Professionals - Rosyidah; Tri Hastuti Nur Rochimah; Hajar Nur Setyowati; Umi Khoirul Bariya (Nusantara Science and Technology Proceedings, 2026)
Background: Background: Inclusive health services are essential to ensure equitable access to healthcare, particularly for vulnerable and underserved populations. However, barriers related to accessibility, communication, infrastructure, and healthcare workforce capacity continue to hinder the implementation of inclusive services in Indonesia. This study evaluated the effectiveness of an Inclusive Health Service Training programme in improving healthcare professionals’ knowledge and readiness to implement inclusive healthcare practices. Methods: A quasi-experimental one-group pre-test and post-test evaluation was conducted during a hybrid Inclusive Health Service Training programme in Yogyakarta, Indonesia, on 21–22 November 2024. The programme involved 120 healthcare professionals from Muhammadiyah and ‘Aisyiyah healthcare facilities. Knowledge was assessed before and after the training using structured questionnaires covering inclusive health service principles, accessibility standards, healthcare regulations, ethical healthcare practices, and inclusive service delivery. Results: Improvements were observed across all domains of inclusive healthcare services, including rights and legal framework (78.4% to 100.0%), accessibility standards (72.5% to 95.2%), healthcare access barriers (68.6% to 90.5%), ethical healthcare practice (86.3% to 95.2%), and inclusive service flow (70.6% to 95.2%). The greatest improvement was found in inclusive service flow (+24.6%). These findings indicate that the training strengthened healthcare workers’ competencies in delivering equitable, accessible, and person-centered healthcare services and supported ongoing efforts by ‘Aisyiyah to advance disability-inclusive healthcare across its healthcare network. Conclusion: The training effectively and significantly improved healthcare workers’ knowledge and readiness to implement inclusive healthcare services, highlighting the importance of continuous capacity building to support equitable healthcare access for persons with disabilities and other vulnerable populations.